Therapeutic outcomes of mycophenolate mofetil and glucocorticoid in thyroid-associated ophthalmopathy patients - Li, Lan-Fang; Xue, Jun-Li; Guan, Lei; Su, Fan-Fan; Wang, Hong; Zhang, Ding-Fu (Frontiers in Endocrinology, 2023)
Objective:To analyzing the efficacy of MMF and glucocorticoid in patients with TAO. Methods:60 patients with TAO were divided into experimental group (n=30) and control group (n=30) by random number table method.Control group was given glucocorticoid pulse therapy while experimental group was given MMF and glucocorticoid. CAS, QOL, visual acuity, eyelid fissure width,intraocular pressure and degree of exophthalmos were observed at the time of admission,the 12th and 24th week.Compare TRAb、IL-6、CD4+/ CD8+ before treatment and 24th weeks, and the clinical therapeutic effect was evaluated. Results:The 12th and 24th week clinical effective rate of experimental group(73.3%，83.3%) was higher than control group（46.7%，60.0%）(P<0.05). At the 12th week of control group, CAS、eyelid fissure width、right visual acuity were improved compared with before treatment.The QOL、visual acuity、CAS、eyelid fissure width、degree of exophthalmos were improved compared with before treatment in control group after 24 weeks，and QOL、CAS、degree of exophthalmos were better than 12 weeks. At the 12th week of experimental group,the QOL、visual acuity、CAS、intraocular pressure、eyelid fissure width and degree of exophthalmos were improved compared with before treatment.These parameters were improved compared with before treatment and 12th week after 24 weeks treatment，and QOL、CAS、degree of exophthalmos is better than 12 weeks.At 12th week,right visual acuity,right intraocular pressure and left eyelid fissure width of experimental group were improved compared with control group（P＜0.05）. At 24th week, the QOL、visual acuity、intraocular pressure、eyelid fissure width、degree of exophthalmos were improved compared with control group（P＜0.05）.There were no differences in ratios of TRAb、IL-6、CD4+/CD8+ between two groups before treatment (P>0.05), These parameters in experimental group was lower than that before treatment and control group after 24weeks 'treatment. Conclusion: MMF combined with glucocorticoid can increase the clinical efficacy of TAO.